EKONOMI KREATIF SEBAGAI BASIS CITY BRANDING MENUJU KEPARIWISATAAN TERINTEGRASI DI KAWASAN DANAU TOBA (CREATIVE ECONOMY AS BASIS OF CITY BRANDING TOWARD INTEGRATED TOURISM IN TOBA LAKE ZONE) - Rosmawaty Sidauruk (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
City branding can refer to the expansion / development of creative economic activities. The development of regional potential based on the creative economy will create creative classes and communities. Creative economy can be a reference for regional development and development. This study aims to stimulate the creation of city branding based on the creative economy, especially for the development of tourism in the area located in the Lake Toba Region. In addition, to determine the existence of creative economic sub-sectors that have the potential for tourism development, increase community income, and trigger regional competitiveness. This study is qualitative descriptive and uses a case study method in the study area of ​​North Tapanuli Regency and Dairi Regency. The results of the discussion concluded that the existence of a creative economy has given rise to economic added value, even the occurrence of social, cultural and civilization transformation in the perspective of human development. Therefore, the creative economy can be a major component of city branding. The existence of city branding accelerates regional progress, especially in areas dominated by tourism areas. It is recommended that each region has a city branding to be more effective and productive in promoting and marketing their potential or superior products. Local governments in the Lake Toba Region are urged to collaborate with the regions and collaborate in integrating tourism development policies, programs and activities with reference to city branding based on creative economy. Keywords: creative economy, city branding, integrated tourism, Toba Lake Area